GROWTH AND RESULT OF COULIHOWES WITH GIVING DUCKS MANURE ON PEAT SOIL - Cundai, Cundai; Sasli, Iwan Sasli; Abdurrahman, Tatang Abdurrahman (Jurnal Sains Pertanian Equator, 2021)
ABSTRACKThis study aims to obtain the best dose of duck droppings to support the growth and results of flower cabbage on peat soil. This research was carried out at a location located in theVillage of Kapur Komplek Kota Raya, starting from December-February 2021. This study useda completely randomized design (CRD) consisting of 5 treatments and 5 replications, eachreplication consisting of 4 samples so the total number of plants was 100 plants. The treatmentswere: P1 = 250 grams/polybag duck droppings equivalent to 10 tons/ha, P2 = 375 grams/polybagduck droppings equivalent to 15 tons/ha, P3 = 500 grams/polybag duck droppings equivalent to20 tons /ha, P4 = 625 grams/polybag duck droppings equivalent to 25 tons/ha, P5 = 750grams/polybag duck droppings equivalent to 30 tons/ha. Observational variables in this studywere root volume (cm3), plant dry weight (g), flower/crop diameter (cm), and flower weightper/plant (g). The results showed that the provision of duck droppings had no significant effecton observational variables such as root volume, plant dry weight, flower diameter, and flowerweight.Key words : duck droppings, peat soil, flower cabbage plants